2018
DOI: 10.1186/s13550-018-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 receptor density is negatively correlated with neural activity related to working memory in humans

Abstract: BackgroundThe histamine H3 receptor is regarded as a drug target for cognitive impairments in psychiatric disorders. H3 receptors are expressed in neocortical areas, including the prefrontal cortex, the key region of cognitive functions such as working memory. However, the role of prefrontal H3 receptors in working memory has not yet been clarified. Therefore, using functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) techniques, we aimed to investigate the association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Interestingly, and in agreement with the latter observations, H1R antagonist but not H2R antagonist was found to impair working memory, while H3R antagonist/inverse agonist clobenpropit was reported to improve cognitive functions in preclinical studies in rodents ( Nakazato et al, 2000 ; Huang et al, 2004 ). In addition, and in a clinical study, the density of H3Rs in the dorsolateral prefrontal cortex was inversely correlated with performance in the working memory paradigm ( Ito et al, 2018 ).…”
Section: Neurological Manifestations and Application Of Several H3r A...mentioning
confidence: 98%
“…Interestingly, and in agreement with the latter observations, H1R antagonist but not H2R antagonist was found to impair working memory, while H3R antagonist/inverse agonist clobenpropit was reported to improve cognitive functions in preclinical studies in rodents ( Nakazato et al, 2000 ; Huang et al, 2004 ). In addition, and in a clinical study, the density of H3Rs in the dorsolateral prefrontal cortex was inversely correlated with performance in the working memory paradigm ( Ito et al, 2018 ).…”
Section: Neurological Manifestations and Application Of Several H3r A...mentioning
confidence: 98%
“…Human studies provide further evidence for a potential role of the H3R in cognitive function and schizophrenia. A multi-modal study combining positron emission tomography (PET) with functional magnetic resonance imaging (fMRI) in healthy controls found a negative correlation between uptake of an H3R-specific tracer and the blood oxygen level dependent signal in the right dorsolateral prefrontal cortex (DLPFC), during a working memory task ( Ito et al, 2018 ). Additionally, a post-mortem study of patients with schizophrenia found an increase in H3R expression in the DLPFC compared to healthy controls and reported a positive correlation between receptor expression and psychotic symptom severity ( Jin et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 Such neurotransmitters are essential for the normal operation of the brain. 5,16,17 Evidence from animal studies and postmortem human brain analysis suggests that the H 3 receptor is involved in several normal physiological processes and diseases or disorders of the brain, such as cognition, 5,18 anxiety, 19 sleep disorders, 16 obesity, 20 Alzheimer's disease, Parkinson's disease, schizophrenia, attention deficit hyperactive disorder, and epilepsy. 16,21−23 Pharmacological studies have shown that blocking the constitutive activity of H 3 receptors by the administration of an inverse agonist or antagonist enhances the release of histamine and may have therapeutic relevance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Histamine release in the mammalian brain shows a diurnal rhythm, with a low rate during sleep and a high rate during waking, active state. , H 3 receptors can also form heteroreceptors, which can modulate the release of other neurotransmitters, including acetylcholine, dopamine, , noradrenaline, , serotonin, , and gamma-aminobutyric acid . Such neurotransmitters are essential for the normal operation of the brain. ,, …”
Section: Introductionmentioning
confidence: 99%